On the Influence of Walt Whitman’s Poetry in China - Song, Siling; Lv, Yuan; Li, Jing; Wu, Fang (Transactions on Social Science, Education and Humanities Research, 2024)
Walt Whitman is one of the most world renowned poets whose poems exert great influence to the poets worldwide, including Chinese poets. This thesis here tries to analyze the influence that Whitman has exerted to both literature and social structure in China. On the whole, the thesis starts with introduction of the great poet and then talks about three representative poets whose works have been greatly influenced by Whitman. They are Tian Han, Guo Moruo, and Hu Shih. Tian is the first person who introduced Whitman to China; Guo wanted to get rid of the old form and to try something new in style; Hu was one of the leading vanguards in the May-Fourth Movement. In addition, due to the influence of Whitman, some poetic schools were created which celebrated the ideology of democracy and freedom. The thesis here mentions three poetic schools: the Revolutionary Poetry School, the July Poetry School, and the Crescent Moon Poetry School.